Promoting Human Dignity and the Common Good - Kanali, James (Asian Horizons, 2023)
The concept of human dignity seems to require, in and of itself, some privileged “places” and “ways” of exercising it. In many countries, people do not enjoy equal access to basic services and resources, nor are they given the possibility to participate in public decision making. This particularly affects the lives of poor and marginalized groups. As I argue further, exclusion and discrimination are perpetuators of poverty and provoke social tensions and conflict. In fact, all policies, programmes, and technical assistance should foster the realization of Human Rights as laid down in the International Bill of Human Rights. This Human Rights Based Approach (HRBA) promotes the concept of responsible governments, with the obligation to respect, protect and fulfil the human rights of their citizens. People are active citizens entitled to rights rather than depend on their government’s mercy or the goodwill of international support. And people are expected to respect other human beings’ rights – the same rights as they enjoy themselves.